Doing different things or doing it differently?: rice intensification practices in 13 states of India - Kuppannan, Palanisami; Karunakaran, K.R.; Amarasinghe, Upali A.; Ranganathan, C.R. (2013)
Can the System of Rice Intensification be the answer to meet the country's future rice demand? A macro-level study covering 13 major rice-growing states indicates that fields with SRI have a higher average yield compared to non-SRI fields. Out of the four core SRI components typically recommended, 41% adopted one component, 39% adopted two to three components, and only 20% adopted all the components. Full adopters recorded the highest yield increase (31%), but all adopters had yields higher than those that used conventional practices. They also had higher gross margins and lower production costs compared to non-SRI fields. Though the rice yield of the country can significantly increase under SRI and modified SRI practices, there are major constraints that have to be tackled before this can be achieved.